Aquaculture and Fisheries Biotechnology Genetic Approaches - Dunham, Rex A (CABI, 2014)
Only 30 years ago, fish culturists and researchers complained of the lack of genetically improved fish, and used this as a justification for increased research in the area of genetic biotechnology. There has been an explosion of research in this area, and now genetics and biotechnology are making a significant impact on aquaculture and fisheries, although potential for much greater progress exists. When improvements from biotechnology are considered, most people think of the impact on aquaculture and not the impact on fisheries. I have tried to address, as the title of this book reflects, not only biotechnology in aquaculture but the interrelationships with fisheries as well. There are several reasons for this. The biochemical and molecular genetic tools that can be applied in aquaculture are equally important for studying population and conservation genetics in fisheries. The goals of aquaculture and fisheries are often portrayed as antagonistic; however, that should not be true and the two cannot be separated because of their interrelationships and impacts on each other. If applied properly, aquaculture has the potential to relieve pressure on natural populations and have positive environmental effects.